Use of Vitamins and their Derivates in the Treatment of Cutaneous Disorders - Chiricozzi, Andrea; Chimenti, Maria Sole; Bavetta, Mauro; Babino, Graziella; Chimenti, Sergio; Saraceno, Rosita (Journal of Nutritional Therapeutics, 2013)
Vitamins represent fundamental substrates for various physiologic functions occurring in human body. This review seeks to highlight their relevance in skin biology and to describe the cutaneous manifestations correlated with their deficiency.